Severe Hyperammonaemia with Metabolic Acidosis in a Neonate a Case Report of Ornithine Transcarbamylase Deficiency (OTCD) - Aniza Mohammed Jelani; Hani Ajrina Zulkeflee; Noor Azlin Azraini Che Soh; Julia Omar; Wan Aireene Wan Ahmed; Muhammad Yusoff Mohd Ramdzan (USIM Press, 2024)
Vol. 8 No. 1 (2022)